Development of Learning Media Kahoot! Based on Gamification in Basic Management Subjects Office and Business Services - Amelia Devi, Dini; Puspasari, Durinda (Jurnal Paedagogy, 2025)
This study aims to analyze the development process, feasibility, and student responses to the development of Kahoot!-based gamification learning media. This research employed a Research and Development (R&D) design using the ADDIE model. The participants consisted of 20 students from Class X MPLB 1 at SMKN 2 Kediri. The research instruments included validation sheets for material and media experts as well as student response questionnaires. Data were analyzed using material and media expert validation analysis and student response analysis. The results showed that the material expert validation obtained a score of 91%, while the media expert validation reached 97%, both categorized as very good. The overall percentage of student responses to the Kahoot!-based gamification learning media was 97%, also classified as very good. Therefore, it can be concluded that the developed Kahoot!-based gamification learning media is highly suitable for use in the teaching and learning process for Class X MPLB students at SMKN 2 Kediri.